RETRACTED: Legal Analysis Of Electronic Information Dissemination That Violates Moral Norms - Grace Geovanni (JURNAL HUKUM SEHASEN, 2023)
RETRACTION NOTICE Following up on the review of articles published in Jurnal Hukum Sehasen carefully, thoroughly, and considering the article entitled "Penegakan Hukum Terhadap Tindak Pidana Perdagangan Anak Serta Hak Restitusinya" Vol 9 No 2 (2023), DOI: https://doi.org/10.37676/jhs.v9i2.4868 This paper was found to violate the publication principles of the Jurnal Hukum Sehasen and has been withdrawn.This article has been withdrawn by the Author and the article withdrawal letter is attached in PDF form.The document and its contents have been removed from the Jurnal Hukum Sehasen, and reasonable efforts should be made to remove all references to this article.